BrainDead. Season one [videorecording (DVD)] - King, Michelle (Television producer); King, Robert (Screenwriter) (CBS, 2016)
When struggling documentary filmmaker Laurel Healy takes a job working with her brother, Senator Luke Healy, she soon discovers there's more to Washington than meets the eye. As tensions grow amongst political parties, so does a conspiracy involving alien bugs replacing the brains of several members of congress. The investigation unfolds while the infection spreads. Whatever's happening, it's clear this isn't politics as usual.